HUBUNGAN ANTARA DISREGULASI EMOSI DENGAN DIGITAL HOARDING PADA DEWASA MUDA - Patricia Irene; Untung Subroto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between digital data hoarding and emotional dysregulation in emerging adulthood. This study was conducted on 276 participants aged 18–25 years. This study used a quantitative correlational research technique to determine whether there is a relationship between emotional dysregulation and digital on emerging adulthood. Based on the results of data processing, it can be concluded that there is a positive and significant relationship between the two variables (r = 0.144 and p = 0.016). This means that the more difficulty someone has in regulating their emotions, the more they will hoard digital data.